Pemberdayaan home industry berbasis kelompok usaha bersama guna meningkatkan pendapatan masyarakat Desa Wiring Tasi - Herman Herman; Adil Setiawan; Chahyono Chahyono (DEDIKASI, 2020)
The implementation of the Community Service Program Community Service Program Community Based Empowerment Community Service Program Community Service Program will increase the Wiring Tasi Village in Suppa District. The results of the consul meeting with partners finally identified 6 issues: (i). The low ability of entrepreneurs in home industry businesses (ii). Business organizations have not been managed optimally, (iii). The business production process has not yet implemented a good manufacturing product, (iv). Home industry products do not yet have a halal quality guarantee / certificate, (v). Packaging has not been able to attract customers, and (vi). Marketing is still limited to orders. Solution to the problem:(i). Entrepreneurship training for home industry players and the general public, (ii). Making the home industry a KUB to encourage synergy between business actors, (iii). Assistance and training related to the production process with the application of good manufacturing products, (iv). Product legality training and assistance, (v). Product packaging design and training and (vi). Assistance and marketing training based on promotion and information technology. Expected outputs from KKN PPM are: (i). Knowledge of home industry and community entrepreneurs is increasing, (ii). The formation of joint business groups in each hamlet, (iii). Implementation of good manufacturing products for home industry players, starting from selecting raw materials, production processes, and post-production, (iv). Increasing the quality of simple technology-based home industry product packaging, (v). Increased product quality assurance with the availability of halal certification for home industry products, (vi). The availability of media promotion of various home industry products, (vii).Increased income of Wiring Tasi villagers